Effects of Holocene climate change, volcanism and mass migration on the ecosystem of a small, dry island (Brava, Cabo Verde). (22nd March 2021) - Castilla‐Beltrán, Alvaro; de Nascimento, Lea; Fernández‐Palacios, José María; Whittaker, Robert J.; Romeiras, Maria M.; Cundy, Andrew B.; Edwards, Mary; Nogué, Sandra
Abstract: Aim: Palaeoecological data provide an essential long‐term perspective of ecological change and its drivers in oceanic islands. However, analysing the effects of multi‐scalar and potentially co‐occurring disturbances is particularly challenging in dry islands. Here, we aim to identify the ecological consequences of the integrated impacts of a regional drying trend, volcanic eruptions and human mass migrations in a spatially constrained environment—a small, dry oceanic island in Macaronesia. Location: Brava Island, Republic of Cabo Verde. Taxa: Terrestrial vegetation and fungi. Methods: We use palaeoecological analyses applied to a caldera soil profile that dates back to 9700 cal yr BP (calibrated years before the present). Analyses include pollen (vegetation history), non‐pollen palynomorphs (changes in fern and fungal communities), grain‐size distribution, loss‐on‐ignition and geochemistry (sedimentology and erosion regimes), microscopic tephra shards (volcanic ash deposition) and charcoal (fire regime). Results: A regional drying trend after c. 4000 cal yr BP caused increased erosion but had limited immediate impacts on highland grassland vegetation. The expansion of fern‐rich woody scrubland was contemporaneous with significant deposition of volcanic ash and erosion between 1800 and 650 cal yr BP. About 300 cal yr BP, exogenous plants expanded, grazing and fires increased, and there was a decrease of native vegetation cover. Main conclusions: Throughout the Holocene, highland vegetation in Brava was characterized by the presence of open landscapes dominated by herbaceous species (e.g. Poaceae, Forsskaolea ), with some presence of woody native taxa (e.g. Ficus, Dodonaea ). A regional drying trend was a driver of erosion since the Mid Holocene but did not have an immediate influence on highland vegetation. Tephra deposition is a possible driver of vegetation change. Inter‐island mass migration after volcanic events in Fogo Island c. 1680 CE potentially triggered land use change and intensification, causing a reduction of native vegetation in Brava.